The Impact of Language and Response Format on Student Endorsement of Psychological Misconceptions. (January 2013) - Hughes, Sean; Lyddy, Fiona; Kaplan, Robin
The present study examined the possibility that the language and response format used in self-report questionnaires influences how readily people endorse misconceptions. Four versions of a 40-item misconception test were administered to European ( n = 281) and North American ( n = 123) psychology and nonpsychology undergraduates. Response format and ambiguity of phrasing were manipulated. Results indicate that misconception endorsement was strongly influenced by both question phrasing and response format, with students showing more agreement and less disagreement when misconceptions were ambiguously phrased or a 7-point rating scale used. These procedure-related effects were observed for European and North American psychology and nonpsychology students alike irrespective of the amount of time they had spent studying the subject. Implications for designing pedagogical procedures to assess student's disciplinary knowledge and beliefs are discussed.